La migration singulière des adoptés dans l’espace euro-américain depuis 1945 - Yves Denéchère (Amnis)
International adoption is a singular type of migration that entails a change of country and often of cultural milieu for the children. Since the end of World War II, the trans-Atlantic space has witnessed adoptive movements involving transnational mobility between Europe, North America and Latin America. Tens of thousands of European and American children have thus crossed the Atlantic in both directions, with each decade corresponding to a particular flow and historical context. International adoption involves a twofold social ascension for the children who leave a developing country for a developed country and a poor family for one in a more comfortable financial situation. These particular migratory currents, seldom studied as such, influence the interactive representations of the populations and countries involved in this often very unequal relationship. As adopted children become integrated into their receiving countries they often forget, reject or negate their origins. Nevertheless, a tie remains and, as the years pass, it evolves, restructures and reconstructs itself. As adults, the adoptees can be considered as veritable intercultural actors in the trans-Atlantic space.